Nonlethal Levels of Zeaxanthin Inhibit Cell Migration, Invasion, and Secretion of MMP-2 via NF-κB Pathway in Cultured Human Uveal Melanoma Cells - Ming-Chao Bi; Nicole Hose; Cai-Lian Xu; Chen Zhang; Jodi Sassoon; E. Song (Journal of Ophthalmology)
Zeaxanthin at nonlethal dosages (3–10 μM) significantly inhibited the cell migration of cultured uveal melanoma cells (C918 cell line) as determined by wound healing assay and Boyden chamber assay. Matrigel invasion assay showed that cell invasion of uveal melanoma cells could be significantly inhibited by zeaxanthin. Secretion of MMP-2 by melanoma cells was significantly inhibited by zeaxanthin in a dose-dependent manner as measured by ELISA kit. Zeaxanthin also significantly inhibited the NF-κB levels in nuclear extracts of the UM cells, which is the upstream of the MMP-2 secretion. These results suggest that zeaxanthin might be a potentially therapeutic approach in the prevention of metastasis in uveal melanoma.